Plastic Optical Fiber Sensor for Sensing Refractive Index of Citric Acid Based on Surface Plasmon Resonance - Mohammed Jassam, Ghufran; K. Abdaldeen, Zeinah; M. Taboor, Reem; M. lbraheim, Sara; Benchaabane, Aida (Al-Nahrain Journal of Science, 2024)
Using plastic optical fiber with multimode (MPOF), optical fiber sensor (OFS) based on Surface Plasmon Resonance (SP.R) was created and put into use. The sensor is used to determine performance metrics including of Signal to noise ratio (SNR), Sensitivity (S), Figu.re of merit (FOM), and Resolution(R) in addition to detecting and measuring the refractive index of different concentrations of citric acid. With a sensing region exposed to 50 nm of gold (Au) metal layer, the optical fiber-based SPR sensor was found to have a sensitivity value of 1250nm, an SNR of 0.27, a figure of merit of 93.3 and a resolution 80000.